Kajian Teologis Praktis Tentang Tanggung Jawab Penatua Dan Implementasinya Terhadap Pelayanan Di Gereja Protestan Persekutuan (GPP) Desa Dolok Sait - Ester Simanjuntak; Hanna Dewi Aritonang; Jungjungan Simorangkir (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Elders in GPP Dolok Sait village have not fully carried out their duties and responsibilities, so this research aims to examine practical theological studies regarding elder responsibilities and their implementation in services at GPP. The qualitative research method is a descriptive approach. This research shows that elders do not understand their duties and responsibilities, especially in being role models. It is hoped that the synod and pastors will provide guidance for elders and pay attention to the elders' welfare so that the congregation does not feel lazy about replacing elderly elders.